Discussion - OF Mr. Mathewson's Paper on Relative Elimination of Iron, Sulphur and Arsenic in Bessemerizing Copper-Mattes (see p. 154) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1908)
Prof. Henry M. Howe, New York, N. Y. (communication to the Secretary*):—The results presented in Mr. Mathewson's paper are of very great interest. Perhaps the most interesting is that shown in Table I. and Fig. 1, in which the arsenic decreases in 10 min. from 0.22 to 0.07 per cent. This is such a large decrease that it is to be hoped that Mr. Mathewson will verify it by repeating his tests with a matte of similar composition. This is particularly to be desired, because the simultaneous removal of sulphur appears to be very small. All three blows further agree in showing that the removal of arsenic is in the very early part of the blow. The fact that the removal of arsenic then ceases abruptly cannot be explained completely by the fact that the arsenic has fallen so low as by its lowness to resist further removal, because in the first blow the arsenic becomes stationary at 0.06 per cent., whereas in the third blow it does not become stationary until it has fallen to 0.034 per cent. The abrupt ending of the removal of arsenic is more likely to find its explanation in the composition of the slag, and it is to be hoped that Mr. Mathewson will supplement these extremely valuable data with others in which the composition of the slag at the same time shall be given. The sudden rise of arsenic toward the end of the third blow I suppose must be referred to an error in sampling or analysis.